2017
DOI: 10.1016/j.kint.2017.05.034
|View full text |Cite
|
Sign up to set email alerts
|

The hallmarks of mitochondrial dysfunction in chronic kidney disease

Abstract: Recent advances have led to a greater appreciation of how mitochondrial dysfunction contributes to diverse acute and chronic pathologies. Indeed, mitochondria have received increasing attention as a therapeutic target in a variety of diseases since they serve as key regulatory hubs uniquely situated at crossroads between multiple cellular processes. This review provides an overview of the role of mitochondrial dysfunction in chronic kidney disease (CKD) with special emphasis on its role in the development of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
305
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(341 citation statements)
references
References 42 publications
6
305
0
7
Order By: Relevance
“…Previous studies have suggested that MtD is mainly observed in acute kidney injury and CKD [28,29]. Our previous study demonstrated that NLRP3 deficiency may attenuate renal fibrosis by improving MtD in a mouse unilateral ureteral obstruction model for CKD [22].…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have suggested that MtD is mainly observed in acute kidney injury and CKD [28,29]. Our previous study demonstrated that NLRP3 deficiency may attenuate renal fibrosis by improving MtD in a mouse unilateral ureteral obstruction model for CKD [22].…”
Section: Discussionmentioning
confidence: 87%
“…The most elaborated is undoubtedly the role of OS in diabetic nephropathy. In this specific context, increased OS has been shown to be due to multiple mechanisms including mitochondrial dysfunction, increased NOX activity, eNOS uncoupling, and deficiencies in antioxidant defense mechanisms, both enzymatic and nonenzymatic, for which we refer to extensive reviews by several groups [54,56].…”
Section: Polyphenols-flavonoidsmentioning
confidence: 99%
“…In CKD, increased mitochondrial ROS generation and mitochondrial dysfunction are frequently reported. Especially in diabetic nephropathy, mitochondrial dysfunction has been well explored with findings on both morphological as well as functional disturbances in the renal mitochondria [56]. But also in nondiabetic CKD patients, disturbed regulatory MiRNAs such as MiR21 have been reported in CKD patients and an impaired complex IVactivity has been reported [57,59].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Movement of foot processes in response to environmental changes requires the redistribution of actin filaments which is dependent upon phosphorylation-mediated signalling. Mitochondrial dysfunction with insufficient ATP production may contribute to the development of DN [52][53][54]. Mitochondria and glycolysis maintain energy homeostasis in podocytes [41,51], with glycolysis responsible for the intracellular ATP distribution in the cortical area of podocytes [41].…”
Section: Discussionmentioning
confidence: 99%